De l’engagement dans la fonction d’adjoint d’établissement scolaire à l’exercice partagé du pouvoir et de l’autorité - Simon Mallard; Gwénola Réto; Rozenn Décret-Rouillard (Recherches en Éducation)
Intermediate school administration is a major lever for the implementation of educational policies. The international literature is abundant and generally aims to document the function of head teachers without dissociating them from their vice assistants. Yet, the population of vice assistants is the one that is not addressed by these questions. This article focuses on the commitment of education and teaching professionals to the role of school assistant. The analysis of semi-structured interviews conducted with public education vice assistants revealed three main themes : becoming involved in order to take on responsibilities, going through trials and tribulations, and finally taking on the role in order to become the head teacher. These mains make it possible to qualify the commitment to the function of vice assistant and to understand what appears to be the backbone of their function : the shared exercise of power and authority with the head teacher.